2017
DOI: 10.1016/j.stemcr.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

PSEN1 Mutant iPSC-Derived Model Reveals Severe Astrocyte Pathology in Alzheimer's Disease

Abstract: SummaryAlzheimer's disease (AD) is a common neurodegenerative disorder and the leading cause of cognitive impairment. Due to insufficient understanding of the disease mechanisms, there are no efficient therapies for AD. Most studies have focused on neuronal cells, but astrocytes have also been suggested to contribute to AD pathology. We describe here the generation of functional astrocytes from induced pluripotent stem cells (iPSCs) derived from AD patients with PSEN1 ΔE9 mutation, as well as healthy and gene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
265
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 265 publications
(299 citation statements)
references
References 65 publications
17
265
3
3
Order By: Relevance
“…Consistent with increased ER-mitochondrial calcium signaling and oxidative phosphorylation, young adult sel-12 mutants display elevated oxygen consumption rates and increased levels of ROS (Sarasija et al, 2018). Strikingly, similar elevation in oxygen consumption rates and ROS levels were observed in functional astrocytes from induced pluripotent stem cells (iPSCs) derived from AD patients with PSEN1 mutations suggesting a conserved role for presenilin in mitochondrial respiration and ROS homeostasis (Oksanen et al, 2017). Taken together, these data indicate that presenilin mutations cause increased ER-calcium release, subsequent mitochondrial calcium uptake and concomitant increase in mitochondrial respiration, which results in overproduction of ROS.…”
Section: Calcium Homeostasis and Mitochondrial Function Is Disrupted mentioning
confidence: 78%
See 2 more Smart Citations
“…Consistent with increased ER-mitochondrial calcium signaling and oxidative phosphorylation, young adult sel-12 mutants display elevated oxygen consumption rates and increased levels of ROS (Sarasija et al, 2018). Strikingly, similar elevation in oxygen consumption rates and ROS levels were observed in functional astrocytes from induced pluripotent stem cells (iPSCs) derived from AD patients with PSEN1 mutations suggesting a conserved role for presenilin in mitochondrial respiration and ROS homeostasis (Oksanen et al, 2017). Taken together, these data indicate that presenilin mutations cause increased ER-calcium release, subsequent mitochondrial calcium uptake and concomitant increase in mitochondrial respiration, which results in overproduction of ROS.…”
Section: Calcium Homeostasis and Mitochondrial Function Is Disrupted mentioning
confidence: 78%
“…Moreover, reduction of ER-mitochondrial calcium signaling reduces the levels of ROS observed in sel-12 mutants (Sarasija et al, 2018), indicating that the high ROS production in sel-12 mutants is caused by increased ER to mitochondria calcium transfer. Similar to the astrocytes from iPSCs derived from EOFAD patients harboring PSEN1 lesions (Oksanen et al, 2017), fibroblasts isolated from EOFAD patients harboring different PSEN1 mutations also showed elevated levels of ROS (Sarasija et al, 2018). Moreover, it was found that blocking mitochondrial calcium uptake in these cells using the mitochondrial calcium uniporter inhibitor, Ru360, could suppress the elevated ROS levels observed in the EOFAD patient fibroblast.…”
Section: Oxidative Stress Mediated Neurodegeneration In Sel-12 Mutantsmentioning
confidence: 80%
See 1 more Smart Citation
“…Using this model, atrophy of astrocytes and abnormal expression of astrocytic markers were demonstrated in iPSC-derived astrocytes from patients with familial and sporadic forms of AD [54]. We have also shown that iPSC-derived AD astrocytes are compromised in neuronal supportive function, and display increased β-amyloid production and oxidative stress, altered cytokine release, and dysregulated Ca2+ homeostasis [67]. In addition to cellular models, human post-mortem brain from AD patients also can be used for the study astrocytic pathology at the disease end stage.…”
Section: Astrocytes In Alzheimer's Diseasementioning
confidence: 79%
“…The epigenetic identity of the starting cell population and remnant signaling cues present during the fibroblast-to-iN transition state finally determine subtype identity [23,34]. While these advances clearly offer novel tools to better understand neurological diseases, there is very strong evidence that classical neuronal diseases do not only affect neurons, but involve many cell types represented in the human brain [84]. Both Ngn2 and Ascl1 seem to leave significant 'wiggle room' for subtype specification, which suggests addition of subtype-specifying TFs to the mix for direct iN conversion into the neuronal cell type of interest (Fig.…”
Section: Subtype-specific In Conversionmentioning
confidence: 99%